The predictive role of PD-L1 expression and CD8 + TIL levels in determining the neoadjuvant chemotherapy response in advanced ovarian cancer - T. Aliyeva; B. Y. Aktas; F. Gundogdu; E. Chalabiyev; Z. Arik; A. Usubutun (Journal of Ovarian Research)
Abstract Objective To analyze how the PD-L1 expression and CD8 + tumor infiltrating lymphocyte (TIL) levels in biopsy samples before neoadjuvant chemotherapy (NACT) can predict chemotherapy response score and survival for advanced high-grade serous ovarian cancer (HGSC). Methods We retrospectively analyzed 45 patients with advanced epithelial ovarian cancer between 2010 and 2018, who had received at least three cycles of NACT. PD-L1 expression and CD8 + TIL levels were evaluated by immunohistochemical staining in the pre-NAC tumor samples from which the patients had been diagnosed. The post-NACT tissue samples taken during interval debulking surgery (IDS) were used to evaluate the chemotherapy response score (CRS). Results Among all the patients, CRS 1 (no response) was found in 8 patients, CRS 2 (partial response) in 28 patients, and CRS 3 (complete response) in 9 patients. A total of 20 (44.4%) patients had high intratumoral CD8 + TILs (iCD8 + TILs) levels, and 35 (77.8%) patients had high expression stromal CD8 + TILs (sCD8 + TILs). No statistically significant relationship was found between high and low expression of i/s CD8 + TILs levels with PFS and CRS. The study found that 33 (73.3%) patients had high levels of stromal PD-L1 (sPD-L1) expression and 28 (62.2%) patients had high levels of intratumoral PD-L1 (iPD-L1) expression. In the iPD-L1 group, patients with low expression had a PFS of 28 months, whereas those with high expression had a PFS of 17 months (p = 0.028). Among the patients with high iPD-L1 expression, 23 (82.1%) patients showed CRS2, 4 (14.3%) showed CRS3, and only 1 (3.6%) showed CRS1 (p < 0.001). However, high or low expression sPD-L1 did not significantly affect PFS and CRS (p = 0.928 and p = 0.305; respectively). Conclusions We found that iPD-L1 expression levels in diagnostic biopsy in ovarian cancer can predict the chemotherapy response score in interval debulking surgery.